Modelling Projected Changes in Soil Water Budget in Coastal Kenya under Different Long-Term Climate Change Scenarios - Were, Cornelius; Greggio, Nicolas; Giambastiani, Beatrice Maria Sole; Wambiji, Nina; Nzeve, Julius; Antonellini, Marco (Multidisciplinary Digital Publishing Institute, 2020)
The possible impacts that climate change will have on soil water budget and specifically on deep percolation, runoff and soil water content have been investigated using HYDRUS, a methodology based on numerical modelling simulations of vertical water movement in a homogenous soil column on a flat surface. This study was carried out on four typical soil types occurring on the Kenyan coast and the adjacent hinterlands of up to an elevation of 200 m above sea level (m a.s.l.) covered by five weather stations (two dry and three wet stations). Results show that deep percolation and runoff are expected to be higher in 2100 for both Relative Concentration Pathways (RCPs) 2.6 and 8.5 scenarios than they were for the reference period (1986–2005). The average deep percolation is expected to increase by 14% for RCP 2.6 and 10% for the RCP 8.5, while the average runoff is expected to increase by 188% and 284% for the same scenarios. Soil water content is expected to either increase marginally or reduce depend in the same scenarios. The average soil water content is also expected to increase by 1% in the RCP 2.6 scenario and to decrease by 2% in the RCP 8.5 scenario. Increase in deep percolation through clay soil is expected to be the largest (29% in both scenarios), while sandy and sandy clay soil are expected to be the least influenced with an average increase of only 2%. Climate change is expected to impact runoff mostly in sandy soils, whereas the least affected would be clay loam soils. These results further support the assertion that the change in climate is expected to impact the recharge of aquifers by triggering an increase in infiltration under both scenarios.
Keywords: Soil water storage; Recharge; Climate change; Soil; Hydrus